2018
DOI: 10.1037/fam0000439
|View full text |Cite
|
Sign up to set email alerts
|

Desires and intentions for fatherhood: A comparison of childless gay and heterosexual men in Germany.

Abstract: The present study explores the motivation for fatherhood in a sample of childless German gay and heterosexual men aged 18 to 40 years (N = 628 + 638). Referring to the theory of planned behavior (TPB), three potential predictors were considered: the individual's attitude toward having children, perceived attitudes of significant others toward fatherhood, and anticipated parental self-efficacy. Regarding fathering motivation, the general desire to become a father was differentiated from the more concrete father… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 67 publications
(112 reference statements)
5
37
1
1
Order By: Relevance
“…There has been limited research using the TPB among sexual minority childfree people. In a study of childfree heterosexual and gay men researchers found that attitudes and perceived behavioral control, but not subjective norms, were strong predictors of future parenting intentions among men regardless of sexual orientation (Kranz et al, 2018). In this study, the perceived benefits and costs of parenthood (attitudes), the attitudes of others toward future parenthood (subjective norms), and parenthood self-efficacy were directly associated with fathering intentions of gay men and heterosexual men.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…There has been limited research using the TPB among sexual minority childfree people. In a study of childfree heterosexual and gay men researchers found that attitudes and perceived behavioral control, but not subjective norms, were strong predictors of future parenting intentions among men regardless of sexual orientation (Kranz et al, 2018). In this study, the perceived benefits and costs of parenthood (attitudes), the attitudes of others toward future parenthood (subjective norms), and parenthood self-efficacy were directly associated with fathering intentions of gay men and heterosexual men.…”
Section: Introductionmentioning
confidence: 53%
“…According to the TPB (Ajzen, 1991), an individual's attitudes, subjective norms, and perceived behavioral control or self-efficacy (Bandura, 1997) are important factors in all decision-making processes. Previous studies have demonstrated the TPB could be useful in understanding parenting intentions generally not necessarily in terms of gender or sexual orientation (Ajzen and Klobas, 2013) and among gay and heterosexual men (Kranz et al, 2018). Based on the TPB, parenting intentions would be predicted by an individual's perceived life changes of future parenthood (attitudes), along with his or her personal desire to conform to these social expectations (subjective norms), and perceived control or belief that he or she can become a parent in the future (self-efficacy; Ajzen and Klobas, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations